Conscientious Objection (General Aspects and the Slovenian Regulation of Conscientious Objection to Abortion) - Cerar, Miro (Medicine, Law & Society, 2025)
This article discusses the theoretical aspects of conscientious objection. It is primarily a moral category. In relation to law, it is the disobedience of an individual to certain legal norms (principles and rules) that conflict with the individual’s moral conscience. Conscientious objection differs in several respects from other forms of disobedience to authority, such as civil disobedience. As a moral phenomenon, conscientious objection is first and foremost the inner moral obligation of an individual to resist a particular political, legal or other norm of authority or behaviour. Conscientious objection may also be permitted by law, but to a very limited extent. Conscientious objection can only be defined as a right in a rationalized reflection of morality and, above all, in the sphere of law which is based on the dualism of rights and duties (attributive-imperative character of law). In the article, some important factors for the legal assessment of the (right to) conscientious objection and some fundamental aspects of the Slovenian constitutional and legal regulation of the right to conscientious objection to abortion by a physician are presented in more detail.